Violet phosphorus: an effective metal-free elemental photocatalyst for hydrogen evolution. Issue 92 (2nd November 2022) - Gu, Mengyue; Zhang, Lihui; Mao, Siman; Zou, Yajun; Ma, Dandan; Shi, Jianwen; Yang, Na; Fu, Chengcheng; Zhao, Xuewen; Xu, Xuequan; Cheng, Yonghong; Zhang, Jinying
Abstract : Layered violet phosphorus, the most stable phosphorus allotrope, has been demonstrated to have excellent photocatalytic activity for hydrogen evolution reactions. Abstract : Violet phosphorus, a non-metallic elemental layered structure, has not been reported as a photocatalyst due to the lack of its resources. An excellent photocatalytic H2 evolution rate of 675 ± 109 μmol h −1 g −1 with high stability has been achieved by the violet phosphorus simply dispersed in deionized water with addition of 1.0 wt% of co-catalyst Pt, which is much higher than that obtained from black phosphorus. The H2 evolution rate was observed to reach values as high as 553 μmol h −1 g −1 with addition of 0.5 wt% co-catalyst Pt.